ANALISIS PERBEDAAN PEMAHAMAN KONSEP MATEMATIKA BERDASARKAN GAYA BELAJAR MAHASISWA - Putri Tri Wijayanti; Jesi Alexander Alim; Zakiah Ulya (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This study aims to analyze differences in students’ mathematical conceptual understanding based on visual, auditory, and kinesthetic learning styles. A descriptive quantitative approach with a comparative design was applied using a questionnaire and a concept test, analyzed through non-parametric statistics. The findings reveal no significant differences among learning styles. It is concluded that learning style is not the sole factor, highlighting the need for adaptive teaching strategies and further research with broader scope.